MEDIA PEMBELAJARAN BIOLOGI UNTUK SEKOLAH MENENGAH PERTAMA KELAS VII - Meilina Widiyaningsih; Sri Huning Anwariningsih; Firdhaus Hari Saputro (Universitas Sahid Surakarta, 2013)
ssing system in which teaching and learning are directly face to face. This method has several drawbacks, especially often take a long time in the biology oflearning media. The purpose of this research is to develop systems biology study of existing media. The system developed is a medium for learning biology junior highschool class VII previously performed entirely face to face directly, converted into a computer-based system. This change is necessary in order to facilitate the processing ofbiological learning media properly to avoid the weaknesses that are often found in media learning system manually. Software quality measurement in this study usingMcCall, with the five factors used to assess the accuracy, reliability, efficiency, usability, and maintenance.